2017
DOI: 10.12688/wellcomeopenres.13006.1
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale field evaluation of push-pull system against early- and outdoor-biting malaria mosquitoes in an area of high pyrethroid resistance in Tanzania

Abstract: Background: Despite high coverage of indoor interventions like insecticide-treated nets, mosquito-borne infections persist, partly because of outdoor-biting, early-biting and insecticide-resistant vectors. Push-pull systems, where mosquitoes are repelled from humans and attracted to nearby lethal targets, may constitute effective complementary interventions. Methods: A partially randomized cross-over design was used to test efficacy of push-pull in four experimental huts and four local houses, in an area with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…They however also concluded that mosquito biting protection was mainly offered by the push-subunits, which is similar to the findings of this current study [38]. Additionally, during a recent small-scale field evaluations of push–pull, it was determined that presence of the system at the peri-domestic areas undermined the effects of the odor-baited mosquito landing box (MLB) [14]. However, testing both push-and-pull subunits in this current study did not affect the indoor mosquito biting protection, as this was mainly offered by the push-subunits alone.…”
Section: Discussionsupporting
confidence: 85%
“…They however also concluded that mosquito biting protection was mainly offered by the push-subunits, which is similar to the findings of this current study [38]. Additionally, during a recent small-scale field evaluations of push–pull, it was determined that presence of the system at the peri-domestic areas undermined the effects of the odor-baited mosquito landing box (MLB) [14]. However, testing both push-and-pull subunits in this current study did not affect the indoor mosquito biting protection, as this was mainly offered by the push-subunits alone.…”
Section: Discussionsupporting
confidence: 85%
“…The levels of protective efficacy demonstrated by the treated eave ribbons in this study, could potentially be further improved by adding odour-baited traps or lure and kill technologies so as to achieve high levels of communal level protection beyond the household and personal protection currently observed. Indeed, this has already been demonstrated in small-scale in push–pull approaches [ 43 , 44 ]. A study by Menger et al demonstrated that such push–pull effects may however be greater at community level than in the peri-domestic areas [ 43 ], most likely because of the traps, when placed near houses lure the mosquitoes to the area, potentially increasing risk in the peridomestic space, and but the trapped mosquitoes are killed, thereby reducing overall risk at community level overtime.…”
Section: Discussionmentioning
confidence: 76%
“…This too is in line with a previous study, which involved using the transfluthrin actively dispensed at the peri-domestic areas in a push–pull approach whereby the approach did not significantly reduce An. funestus biting and it increased possibility of mosquito diversion effect [ 44 ]. The unresponsiveness of An.…”
Section: Discussionmentioning
confidence: 99%
“…The likely reason for this is the poor response of mosquitoes to the BGS in the presence of humans. Numerous previous studies on push-pull technologies have demonstrated the higher efficacy of the push than the pull [14,[27][28][29]. While the push-pull system may need further development, the success of the FTPE was encouraging and indicated their potential for the control of arboviral diseases.…”
Section: Discussionmentioning
confidence: 99%